2019
DOI: 10.1097/md.0000000000015906
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hypercapnia may not contribute to postoperative delirium in patients undergoing bronchoscopic intervention

Abstract: This study aimed to investigate the risk factors and whether acute hypercapnia contributes to postoperative delirium (POD) during bronchoscopic intervention under general anesthesia or deep sedation. A prospective study was conducted with 119 consecutive patients who had undergone bronchoscopic intervention between February 2016 and December 2016 at the Emergency General Hospital. Twenty-eight patients (23.8%) were diagnosed with POD. The patients were divided into 2 groups: the POD (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…PaCO 2 is a fundamental determinant of cerebral blood flow, cerebral metabolism and intracranial pressure, which suggests a biologically plausible mechanism for an effect on cognitive function [ 2 , 3 ]. However, to the date, studies assessing the association between hypercapnia and POD have yielded inconsistent and conflicting results [ 8 12 ]. Furthermore a recent observational study suggested that avoidance of end-tidal hypocapnia may be associated with a reduced risk of POD [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PaCO 2 is a fundamental determinant of cerebral blood flow, cerebral metabolism and intracranial pressure, which suggests a biologically plausible mechanism for an effect on cognitive function [ 2 , 3 ]. However, to the date, studies assessing the association between hypercapnia and POD have yielded inconsistent and conflicting results [ 8 12 ]. Furthermore a recent observational study suggested that avoidance of end-tidal hypocapnia may be associated with a reduced risk of POD [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of an increased PaCO 2 on neurologic function is likely complex and both favourable and unfavourable neurologic effects have been described in different clinical settings [ 2 7 ]. Similarly, the association of increased intraoperative PaCO 2 levels and the incidence of post-operative delirium (POD) is unclear, and previous small observational studies have yielded mixed results [ 8 12 ]. Given that POD is common, associated with poor outcomes and may be partly preventable, identifying strategies that reduce its incidence by targeting potential modifiable risk factors such as PaCO 2 appears desirable [ 13 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pearson analysis showed no important factors affecting PaCO 2 and certainly no independent factors, either. Mild hypercapnia may not cause brain injury and only worsen the condition of the brain when PaCO 2 is above 100 mmHg [ 8 , 18 , 19 ]. Thus anesthesiologists did not provide any treatment when the PaCO 2 was a little above 50 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Pearson analysis showed that there were no important factors affecting PaCO 2 , certainly no independent factors either. It had been reported that mild hypercapnia may not cause brain injury and worsen the brain's condition only when PaCO 2 was above 100mmHg 8,18,19 . This is the reason why anesthesiologists didn't do any treatment when PaCO 2 was a little above 50 mmHg.…”
Section: Discussionmentioning
confidence: 99%